2020
DOI: 10.3390/diagnostics10120998
|View full text |Cite
|
Sign up to set email alerts
|

FDG PET/CT Findings of Castleman Disease Assessed by Histologic Subtypes and Compared with Laboratory Findings

Abstract: Castleman disease (CD) is a relatively rare lymphoproliferative disorder and the pathophysiology of the subtypes are incompletely understood. Fluorine-18 fluorodeoxyglucose (FDG) positron emission tomography (PET)/computed tomography (CT) demonstrates the metabolic activity of inflammatory and tumorous conditions. The FDG uptake intensity and sites of involved lesions on FDG PET/CT were assessed by histologic subtypes, and compared to the patient’s hemoglobin, platelet, albumin, and high-sensitivity C-reactive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…As discussed earlier, HV-UCD has been thought to occur predominantly in the mediastinal region, but our study revealed that HV-UCD most common involvement site was in the abdominal cavity. Given the advances in imaging modalities [12], the results of the present study may be closer to the actual lesion distribution of HV-UCD.…”
Section: Clinical Characteristicsmentioning
confidence: 69%
“…As discussed earlier, HV-UCD has been thought to occur predominantly in the mediastinal region, but our study revealed that HV-UCD most common involvement site was in the abdominal cavity. Given the advances in imaging modalities [12], the results of the present study may be closer to the actual lesion distribution of HV-UCD.…”
Section: Clinical Characteristicsmentioning
confidence: 69%
“…iMCD is a rare lymphoproliferative disorder that is characterized by multiple lymphadenopathies with unknown etiology [ 17 ]. In particular, iMCD-NOS is a heterogenous entity, likely including undefined disease [ 11 , 18 , 19 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the size and blood supply of lymph nodes reflected by imaging findings, biopsy results showed reactive hyperplasia in 2 patients. A PET-CT scan was then performed, 24 , 29 taking into account the metabolic activity of the lymph nodes, and a second lymph node biopsy is performed. The final diagnosis is made with a complete lymph node biopsy.…”
Section: Discussionmentioning
confidence: 99%